10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
The goal in selecting these recent articles was to help identify literature that may change the clinical practice of women's health for practitioners in the primary care and general gynecology setting. Articles were identified by reviewing high-impact medical and women's health journals, national guidelines, ACP JournalWise and NEJM Journal Watch. In this Clinical Update, we selected recent publications relevant to the sexual health of women. Specifically, we reviewed guidelines and consensus statements on hypoactive sexual desire disorder (HSDD) and genitourinary syndrome of menopause (GSM), as well as studies around the role of pelvic floor muscle training for GSM and psychological and behavioral health for sexual health in midlife women.